Efektivitas Pembelajaran Agama Islam Pada Peserta Didik Berkebutuhan Khusus - Agus Budiman (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
and learning model, but the most importent is on the ability of teachersto know the opportunities in learning models and how to use it. For learnerswith special needs, learning on Islamic religion requires special approachesand methods for learning in order it can be enjoyed by learners. Anappropriate learning design will allow students to understand teachingmaterials despite they have limitation, both physically or mentally. Thispaper tries to explain some of the Development of Islamic teachings withthe modification methods, allocation of time, the approach and thedevelopment of appropriate learning resources. And this paper concludedthat builds confidence in children with special needs is the main thing todo, and providing learning programs that appropriate with the conditionsof learners, as well as provide opportunities for children with special needsget all their rights.